PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE DIIRINGI TEKA-TEKI SILANG TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS X SMAN I BATANG KAPAS KABUPATEN PESISIR SELATAN - Oktavia, Welly - (Pendidikan Biologi, 2014)
This study is motivated by the lack of the results of class tenth students studying biology at SMAN I Batang Kapas. The low of result student learning is caused less active of student in the learning process, the teachers do not use variations of strategies in learning and learning is centered on the teacher. One way that teachers can apply to solve the problem is the type of active learning strategy everyone is a teacher here that accompanied by a crossword puzzle. This study is aims to determine the effect of the application of the type of active learning strategies everyone is a teacher here that accompanied by crossword puzzles on result of learning biology class tenth at SMAN I Batang Kapas Kabupaten Pesisir Selatan. This research is an experimental studies which using Randomized Control Group Posttest Only Design. The population is all of class tenth at SMAN I Batang Kapas that enrolled in the school year 2013/2014. The results of data analysis is obtained that the result of experiment class are 77.08, the result of control class are 67.48 while tcount is 3.79 and ttable is 1.67. This means that t count> ttable so the hypothesis is accepted. Therefore, it can be concluded that the application of the type of active learning strategies everyone is a teacher here that accompanied by crossword puzzles can improve the result of learning students of class tenth at SMAN I Batang Kapas Kabupaten Pesisir Selatan.